PENGARUH KARAKTERISTIK PERUSAHAAN, KONEKSI POLITIK DAN REFORMASI PERPAJAKAN TERHADAP PENGHINDARAN PAJAK (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK TAHUN 2008-2012) - Mulyani, Sri (Jurnal Mahasiswa Perpajakan, 2014)
Tax is another source of domestic revenue which contributed approximately 70% of the state budget. In order to increase tax revenue, it is necessary precautions to minimize tax avoidance efforts undertaken by the taxpayer. This research aims to examine the influence of firm characteristic consisting of leverage and capital intensity, political connection and tax reform to tax avoidance simultaneously and partial. The type of research used is explanatory research. The sampel method used was purposive sampling. Secondary data obtained from financial statements manufactured corporation and listing on the Indonesian Stock Exchange during the year 2008 until 2012. Multiple regression analysis was conducted using SPSS version 21.00 for windows. The test result showed that the variable leverage, capital intensity, political connection and tax reform take effect simultaneously against tax avoidance. From the result of the analysis of partially known that variable leverage and political connection influential significantly to tax avoidance, while the capital intensity and tax reform did not affect significantly to tax avoidance. Keyword: Tax Avoidance, Leverage, Capital Intensity,Â  Political Connection, Tax Reform